Mobile app-based cognitive decision-making and memory games enhance cognitive function in older adults with mild cognitive impairment - Pumpho, Ampha; Boonsinsukh, Rumpa; Srisim, Kitiyawadee; Kaewsanmung, Supapon; Suwannarat, Phannarin; Keawduangdee, Petcharat (Frontiers in Psychology, 2025)
BackgroundIn present-day society, interactive mobile devices are being more frequently used to bolster the memory capacities of senior individuals with mild cognitive impairment (MCI). However, there is a lack of cognitive training mobile game applications that utilize image processing technologies to assess player behaviors concerning cognitive abilities such as executive functioning, memory retention, discrimination and decision-making, and processing speed.ObjectiveThe purpose of this study was to develop a mobile gaming app and investigate whether cognitive-motor training mobile game applications that use image processing to recognize player actions in relation to cognitive abilities like executive functioning, memory, discrimination, and decision making would improve cognitive performances in older adults with MCI.MethodsWe performed a randomized controlled trial of a mobile game app cognitive training group and control group in 42 older adults with mild MCI. The intervention group (n = 21) spent 30 min/day, 2 days/week for 4 weeks, using the mobile app’s cognitive training game. The control group (n = 21) did not receive any training. All the participants were assessed with the neuropsychological tests before and after training.ResultsFollowing the training, the Training group exhibited significantly greater improvements in Stroop test performance, including increased correct responses (p = 0.02, Cohen’s d = 0.71) and reduced uncorrected errors (p = 0.04, Cohen’s d = −0.67). Moreover, auditory reaction time was significantly enhanced (p = 0.03, Cohen’s d = −0.34) compared with the control group, indicating moderate effect sizes and suggesting clinically meaningful benefits of the intervention.ConclusionA newly developed mobile gaming application is a potential tool for training executive function in older adults with MCI.